Sistem Pemberian Pakan Ikan Hias Otomatis Berbasis Arduino: pakan ikan hias otomtis - Afandi, Achmad; Sufaidah, Siti (Exact Papers in Compilation (EPiC), 2022)
In this study, the authors made a tool to monitor ornamental fish feeders in the aquarium automatically based on a scheduled time and according to the number of doses, so that it can help ease the work of ornamental fish hobbyists. Based on the time used is 08.00 and 17.00 for ornamental fish feed. This system uses an Arduino Uno microcontroller as the main controller, RTC (Real Time Clock) for scheduled feeding, and MotorServo as a feed cover driver. By using the above tool components that support the operation of the tool, the aquarium ornamental fish feeder can automatically work according to the selected schedule that has been set. This makes it easier for hobbyists to care for ornamental fish in the aquarium. And very effective for the development of ornamental fish in the aquarium. Keywords: Fish_feed, RTC, Arduino, MotorServo, ornamental_fish.